EVALUASI HASIL BELAJAR MATA KULIAH TEKNOLOGI ALAT BERAT DI JURUSAN TEKNIK OTOMOTIF FT UNP BERDASARKAN STANDAR EMI LPTK - Wagino Wagino (Pusat Pengembangan Ilmiah dan Penelitian Mahasiswa Universitas Negeri Padang, 2015)
This research was aimed could reveal about program planning and program implementation at Heavy Equipment Technology subject in Automotive Department, Engineering Faculty, Padang State University, which refer to learning result. This research was evaluation research by using discrepancy model. Result of the research showed that program planning component got enough valuation (73,35%). While for program implementation of result section got good valuation (85,86%) and when refer to EMI LPTK Valuation Standard also belong good category (85,71%). Thus, the conclusion of this research could be revealed that for program planning of Heavy Equipment Technology learning program still needed to increase the quality. While for most learning result section in program implementation discrepancy was not occur at Heavy Equipment Technology learning in Automotive Department, Engineering Faculty, Padang State University.